ANALISIS PENERAPAN METODE PENYUSUTAN ASET TETAP UNTUK MENGOPTIMALKAN BEBAN PPH TERUTANG PT WELDINGTON INDONESIA PADA TAHUN 2013 - Priska Patricia; Yuliana Sumadi (Jurnal Akuntansi, 2018)
PT Weldington Indonesia is a trading company for welding and cutting equipments and accessories (iron materials). The Company applies Straight-Line methodology to capitalize its fixed assets. Under Straight-Line methodology, PT Weldington Indonesia’s 2013’s Net Income and Income Tax, were Rp 2,907,835,195, and Rp 646,955,422, whereas under the Declining-Balance method, the Net Fiscal Income and Income Tax were Rp 2,902,350,988 and Rp 645,735,301. In Fiscal Year 2013, the depreciation expense calculation under Straight-Line method resulted to a lower depreciation value and higher Profit Before Tax, compared to the Declining-Balance method. In conclusion, the 2013 Income Tax was lower under Declining-Balance method compared to Straight-Line method.